2020
DOI: 10.1093/trstmh/traa111
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of a community-based care package for people with lower limb disorder caused by lymphatic filariasis, podoconiosis and leprosy in Ethiopia

Abstract: We conducted an implementation research study to integrate a holistic package of physical health, mental health and psychosocial care for podoconiosis, lymphatic filariasis and leprosy into routine healthcare in Gusha cluster, Guagusa Shikudad district, northwest Ethiopia. The healthcare package included training patients in lower limb hygiene and skin care and provision of shoes, hygiene supplies and medication. The implementation activities included training events, workshops, awareness raising, self-help gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…We compared our yields with the study by Casado et al 21 Our search identified all 10 articles which were classified as self-care by Casado et al 21 Five of these articles met our inclusion criteria and they had all been included in our review. We identified an additional 10 articles not included in Casado et al 21 The 15 articles were conducted in the following eight countries-China, [24][25][26] Ethiopia, [27][28][29] Brazil, 30 Nepal, 31,32 Nigeria, 33,34 Indonesia, 35,36 India 37 and Mozambique. 38 All articles but one 26 were published between 2001 and 2021.…”
Section: Arti CL E Se Lec T I On (Se E Prisma Diagram Fi Gure 2)mentioning
confidence: 99%
See 4 more Smart Citations
“…We compared our yields with the study by Casado et al 21 Our search identified all 10 articles which were classified as self-care by Casado et al 21 Five of these articles met our inclusion criteria and they had all been included in our review. We identified an additional 10 articles not included in Casado et al 21 The 15 articles were conducted in the following eight countries-China, [24][25][26] Ethiopia, [27][28][29] Brazil, 30 Nepal, 31,32 Nigeria, 33,34 Indonesia, 35,36 India 37 and Mozambique. 38 All articles but one 26 were published between 2001 and 2021.…”
Section: Arti CL E Se Lec T I On (Se E Prisma Diagram Fi Gure 2)mentioning
confidence: 99%
“…Reviewing the 15 articles, nine studies obtained quantitative data [24][25][26]28,29,[32][33][34]37 and the remaining six utilized exclusively qualitative designs. 27,30,35,36,38,39 Only one of the 9 studies that included quantitative data used a contemporaneous control group and this was not obtained by a process of randomization.…”
Section: Arti CL E Se Lec T I On (Se E Prisma Diagram Fi Gure 2)mentioning
confidence: 99%
See 3 more Smart Citations